ENDOMETRIOSIS-ASSOCIATED INFERTILITY: THE ROLE OF HORMONES AND ITS CORRECTION - Kulyk, I. I.; Khmil, S. V. (International Journal of Medicine and Medical Research, 2021)
Background. Endometriosis-associated infertility (EAI) has a number of specific features, which are crucial in the choice of medical treatment. Objective. The aim of the study is to analyze endocrine profile in women with EAI before and after sclerotherapy and pregravid preparation (PP), which includes a vitamin complex FT 500 plus with inositol and vitamin D3. Methods. The study involved 70 women aged 21-40 years with endometriosis-associated infertility. The comparison group included 30 women with tuboperitoneal infertility. ELISA was used to determine concentrations of Anti-Mullerian hormone (AMH), follicle stimulating hormone (FSH), luteinizing hormone (LH), progesterone and estradiol in blood serum using a standard kit by Diagnostic Systems Laboratories, Inc (USA). During two menstrual cycles the FT 500 plus was prescribed once a day from the 2nd/3rd day of the cycle, vitamin D3 was prescribed at the dose of 2,000 IU for women without its deficiency and in therapeutic doses in case of hypovitaminosis. The sclerotherapy with 95% ethanol solution was performed on the 6th-8th day of menstrual cycle. Results. It was established that in women with EAI undergoing PP and sclerotherapy the level of AMH was lower (by 12.90%) as well as progesterone (by 9.84%), while FSH (by 14.47%), LH (by 21.14%) and estradiol (by 35.55%) was higher compare to the comparison group. At the same time, FSH (by 21.98%), LH (by 32.89%) and estradiol (by 32.23%) concentrations were significantly lower compare to their primary indices before sclerotherapy. Conclusions. Sclerotherapy and PP with a vitamin complex, inositol and vitamin D3 has a positive effect on endocrine profile in women with endometriosis-associated infertility